Analisis Perbandingan Pengaruh Faktor Kemudahan Penggunaan, Faktor Sosial Budaya, dan Kepercayaan Teknologi Terhadap Minat Membayar Zakat dan Infak Menggunakan QRIS: Studi pada Baznas Pesawaran dan Baznas Pringsewu - Rangga Rachmad Prayoga; Ahmad Habibie; Adib Fahri (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research aims to compare the variable effects of ease of use, socio-cultural factors, and technology trust on interest in paying zakat and infaq using QRIS. this research uses a quantitative approach. The results show the validity and reliability side, all variables are valid. The classical assumption test also shows if the data is normally distributed, does not experience multicollinearity problems, and there is no heteroscedasticity, so regression analysis can be done properly. In the T test, it was found that in BAZNAS Pringsewu, the ease of use factor does not have a significant impact on muzakki's interest in paying zakat and infaq through QRIS. In contrast, social and cultural factors, trust in technology have a significant influence. Meanwhile, in BAZNAS Pesawaran, ease of use, socio-cultural factors have a significant effect, while trust in technology has no influence on the interest in paying zakat and infaq using QRIS. Then, the F test results present that simultaneously, all variables have a significant effect on muzakki's interest in using QRIS in both regions. Finally, in the Independent T test, based on the results of the Mann-Whitney U Test, it can be concluded that trust in technology is significantly different between BAZNAS Pringsewu and BAZNAS Pesawaran, where Pringsewu people have more confidence in QRIS than Pesawaran people. And the remaining variables do not show significant differences between the two regions.